A review of moisture buffering capacity: From laboratory testing to full-scale measurement. (10th March 2019) - Cascione, Valeria; Maskell, Daniel; Shea, Andy; Walker, Pete
Highlights: Moisture buffering improves indoor air quality and hygrothermal comfort. The lack of a globally agreed method makes comparisons difficult. Dynamic sorption properties should be quantified by in situ testing. Modelled moisture buffering does not fully represent the performance. A novel method of full scale moisture buffering is required. Abstract: It is important to control indoor humidity level in buildings as it influences occupant's health and comfort. Hygroscopic building materials present great potential to passively regulate air humidity due to their ability to adsorb and desorb moisture. In recent years researchers have focused on this capacity, referred to as Moisture Buffering, as it has the potential to improve indoor thermal comfort and reduce HVAC usage and their consequent energy consumption. However, building designers generally do not consider this property an important factor, due to its unclear influence and difficulty in the quantification of its effects in real buildings. Therefore, it is complicated to develop an appropriate laboratory scale testing. The aim of this paper is to investigate the challenges related to moisture buffering measurement and to examine the approaches adopted by researchers. The significance of this study is to identify discrepancies between existing methods in the evaluation of the dynamic adsorption properties and presents areas for further development in testing.